2020
DOI: 10.1021/acs.jafc.0c06671
|View full text |Cite
|
Sign up to set email alerts
|

Arecanut (Areca catechu L.) Seed Polyphenol-Ameliorated Osteoporosis by Altering Gut Microbiome via LYZ and the Immune System in Estrogen-Deficient Rats

Abstract: Polyphenol can improve osteoporosis and is closely associated with gut microbiota, while the mechanism and the relationship among polyphenol, osteoporosis, and gut microbiota colonization remain unclear. Here, an osteoporosis rat model established by ovariectomy was employed to investigate the improving mechanism of arecanut (Areca catechu L.) seed polyphenol (ACP) on osteoporosis by regulating gut microbiota. We analyzed the bone microstructure, Paneth cells, regulating microbial protein (lysozyme (LYZ)), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…Studies in rodents show promising results for the addition of high-fiber diets and the resultant increase in the gut microbiome production of short-chain fatty acids (SCFA), particularly butyrate [14], the primary metabolites of microbial fermentation in the gut [29]. SCFAs appear to protect against postmenopausal and inflammatory bone loss, repair intestinal barriers, and prevent the development of osteoporosis in mice [30][31][32]. These results seem to translate to studies in human populations, where an association between increased dietary fiber consumption and bone mineral density has been demonstrated [33,34].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…Studies in rodents show promising results for the addition of high-fiber diets and the resultant increase in the gut microbiome production of short-chain fatty acids (SCFA), particularly butyrate [14], the primary metabolites of microbial fermentation in the gut [29]. SCFAs appear to protect against postmenopausal and inflammatory bone loss, repair intestinal barriers, and prevent the development of osteoporosis in mice [30][31][32]. These results seem to translate to studies in human populations, where an association between increased dietary fiber consumption and bone mineral density has been demonstrated [33,34].…”
Section: Lifestyle Modificationsmentioning
confidence: 99%
“…The qRT-PCR experiment was performed basing on the previously reported methods with slight modification [ 36 , 37 , 38 ]. In brief, total RNA was extracted from brain tissues homogenized of mice by Eastep R Super Total RNA Extraction Kit (Promega Biotechnology Co., Ltd., Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…To determine the expression of the gut microbiota flora associated with cognitive impairment, 16s high-throughput sequencing was used to study the changes in the intestinal flora. The method of genomic DNA amplification was the same as in the previous research [ 38 ]. Briefly, the microbial DNA in mouse feces was extracted using QIAamp DNA Stool Mini Kit (Qiagen, Hilden, Germany), and then the purity and concentration of DNA were detected by agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…A relatively short-term study (8 days) involving the use of dietary purified blueberry polyphenols, which are rich in anthocyanin, revealed that polyphenols enhance calcium absorption in ovariectomized rats [ 49 ]. As an interesting anti-osteoporotic mechanism, it was recently reported that arecanut ( Areca catechu L.) seed polyphenol promotes bone formation by altering gut microbiota along with controlling inflammatory reactions [ 50 ]. The seed has also been used in osteoporosis therapy in the field of Chinese medicine.…”
Section: Polyphenol-rich Substances or Extractsmentioning
confidence: 99%